You should substitute `r cos theta` for x and `r sin theta` for y such that:

`w = sqrt(4 - 2x^2 - 2y^2) => w = sqrt(4 - 2(r^2 sin^2 theta + r^2 cos^2 theta))`

Factoring out `r^2 ` yields:

`w = sqrt(4 - 2r^2(sin^2 theta + cos^2 theta))`

Using...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You should substitute `r cos theta` for x and `r sin theta` for y such that:

`w = sqrt(4 - 2x^2 - 2y^2) => w = sqrt(4 - 2(r^2 sin^2 theta + r^2 cos^2 theta))`

Factoring out `r^2 ` yields:

`w = sqrt(4 - 2r^2(sin^2 theta + cos^2 theta))`

Using fundamental formula of trigonometry yields:

`sin^2 theta + cos^2 theta = 1`

`w = sqrt(4 - 2r^2)`

You need to differentiate the function w with respect to r, using chain rule such that:

`(dw)/(dr) = (1/(2sqrt(4-2r^2)))*(d(4 - 2r^2))/(dr)`

`(dw)/(dr) = (1/(2sqrt(4-2r^2)))*(-4r)`

Reducing by 2 yields:

`(dw)/(dr) = ((-2r)/(sqrt(4-2r^2)))`

**Hence, differentiating the given function with respect to r yields `(dw)/(dr) = ((-2r)/(sqrt(4-2r^2))).` **